Strong coupling in 65,67Mn - Liu Xiaoyu; Liu Zhong; Ding Bing (EPJ Web of Conferences, 2018)
Excited states in 63,65,67Mn were studied via in-beam γ-ray spectroscopy following knockout reactions from 68Fe. Similar level schemes, consisting of the 11/2−, 9/2−, 7/2− and 5/2−g,s. level sequence, connected by I → I–1 transitions, were established. Their level structures show features consistent with strongly-coupled rotational bands with K = 5/2.